'If only we knew what they wanted': bridging the gap between student uncertainty and lecturers' expectations - Anna Magyar (Association for Learning Development in Higher Education (ALDinHE), 2011)
It is increasingly accepted that the development of the academic writing required to succeed in higher education is most effective when embedded within the discipline in which students are studying and when integrated with formal teaching. The many initiatives and programmes discussed in this journal suggest a variety of models and collaborations in the move from generic study skills to the integration of writing in the disciplines. As a contribution to this, we discuss the evaluation of an academic writing module for Masters students in the School for International Development at the University of East Anglia. The module was devised collaboratively by the learning developer, subject specialist and postgraduate research students from the department. It was delivered by postgraduate research students, who also participated in its evaluation. The evaluation led to changes not only in the writing module itself but to the main Masters programme. We argue that the post graduate research students played a key role in these changes and that through dialogue between students and the department, academics who were only peripherally involved, nonetheless gained insights about students experience, potentially informing their future practice.